New records of rarely reported species in the Mediterranean Sea (December 2025) - MARGHERITA TOMA; DARYL AGIUS; ERNESTO AZZURRO; MARZIA BO; FABIO CROCETTA; İSMAIL DAL; TOMMASO DELLI CARRI; MEHMET CENGIZ DEVAL; LORIS GALLI; ANDROMACHI GKOULIA; FABIO GRATI; DEMETRIS KOLOKOTRONIS; et al. (Mediterranean Marine Science, 2025)
New records of rarely reported species in the Mediterranean Sea (December 2025)